Phosphatase‐mediated bioprecipitation of lead by soil fungi. (3rd September 2015) - Liang, Xinjin; Kierans, Martin; Ceci, Andrea; Hillier, Stephen; Gadd, Geoffrey Michael
Summary: Geoactive soil fungi were examined for their ability to release inorganic phosphate (Pi ) and mediate lead bioprecipitation during growth on organic phosphate substrates. A spergillus niger and P aecilomyces javanicus grew in 5 mM Pb(NO3 )2 –containing media amended with glycerol 2‐phosphate (G2P) or phytic acid (PyA) as sole P sources, and liberated Pi into the medium. This resulted in almost complete removal of Pb from solution and extensive precipitation of lead‐containing minerals around the biomass, confirming the importance of the mycelium as a reactive network for biomineralization. The minerals were identified as pyromorphite (Pb5 (PO4 )3 Cl), only produced by P . javanicus, and lead oxalate (PbC2 O4 ), produced by A . niger and P . javanicus . Geochemical modelling of lead and lead mineral speciation as a function of pH and oxalate closely correlated with experimental conditions and data. Two main lead biomineralization mechanisms were therefore distinguished: pyromorphite formation depending on organic phosphate hydrolysis and lead oxalate formation depending on oxalate excretion. This also indicated species specificity in biomineralization depending on nutrition and physiology. Our findings provide further understanding of lead geomycology and organic phosphates as a biomineralization substrate, and are also relevant to metal immobilization biotechnologies for bioremediation, metal and P biorecovery, and utilization of waste organic phosphates.